Develop a photoacoustic system for deep tissue imaging - Lim, Hong Quan (Nanyang Technological University, 2021)
Photoacoustic Imaging (PAI) uses both light and sound as medium to produce bioimaging within the human body. It utilizes non-ionizing light source, therefore lower health risk and can be used for longer duration. It is also capable of producing bioimage non-invasively with deep penetration capabilities, allowing doctors to make better diagnosis while reducing the need of cutting open the patient’s body. Hence PAI is a technique that has good prospect in reducing the recovery time of the patient while improving the diagnosis and treatment capabilities of medical experts. In this project, a PAI system capable of in-vivo and in-vitro deep tissue imaging capabilities has been developed and is successful in imaging the blood vessels within a living rat. Improvements are made to previous prototype provided to increase the quality of bioimage formed. As the author focuses on the hardware aspect of the system, this report will focus more on the hardware implementation of the system.